Violent video game effects on children and adolescents theory, research, and public policy - Anderson, Craig Alan, 1952-; Gentile, Douglas A., 1964-; Buckley, Katherine E. (Oxford : Oxford University Press, 2007)
This volume uses General Aggression Model (GAM) as a basis for explaining and predicting effects and changes in aggression related to exposure to violent video games. The authors also describe how a developmental risk and resilience model can be integrated into GAM to enhance our ability to predict long-term changes.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Video games and children; Video games and teenagers; Violence in mass media; Children and violence; Youth and violence; Aggressiveness in children; Aggressiveness in adolescence